Generalized Rational Type Contraction and Fixed Point Theorems in Partially Ordered Metric Spaces - Raji, Muhammed; Rathour, Laxmi; Mishra, Lakshmi N.; Mishra, Vishnu N. (Journal of Advances in Applied & Computational Mathematics, 2023)
In this article, we establish the existence and uniqueness of fixed points for rational type contraction mappings in a metric space that is equipped with a partial order. Our results are shown to improve upon previous results in the literature, and we provide illustrative examples to demonstrate the effectiveness of our approach. Mathematics Subject Classification: 47H10; 54H25.